2003
DOI: 10.1063/1.1563844
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of ZrO2 on silicon

Abstract: Electrical and spectroscopic comparison of HfO 2 / Si interfaces on nitrided and un-nitrided Si (100) Yttrium silicate formation on silicon: Effect of silicon preoxidation and nitridation on interface reaction kinetics The interface of zirconium oxide thin films on silicon is analyzed in detail for their potential applications in the microelectronics. The formation of an interfacial layer of ZrSi x O y with graded Zr concentration is observed by the x-ray photoelectron spectroscopy and secondary ion mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…But the experimental data of ZrO 2 films does not show a similar shoulder [30,31]. In many aspects, ZrO 2 resembles its twin oxide, HfO 2 , though it is generally believed that the electron correlations in ZrO 2 are weaker.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…But the experimental data of ZrO 2 films does not show a similar shoulder [30,31]. In many aspects, ZrO 2 resembles its twin oxide, HfO 2 , though it is generally believed that the electron correlations in ZrO 2 are weaker.…”
Section: Resultsmentioning
confidence: 85%
“…[1,2]. Moreover, ZrO 2 has been proven to have one of the most high dielectric constants [3] and be promising in optical and protective coatings [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Both types of interfacial layers have been reported [10,15,[24][25][26][27]. The interface between interfacial SiO 2 and the high-k layer tends to be rough, and intermixing can be difficult to distinguish from roughness [28].…”
Section: B) Uncapped Anneals Under Conditions That Favor Reaction (1)mentioning
confidence: 99%
“…For example, the precise chemistry of SiO 2 -like interfacial layers formed between ZrO 2 or HfO 2 gate dielectrics and the Si substrate interface under oxidizing deposition conditions is still under debate. Electrical measurements show that the dielectric constant of these interfacial layers is greater than that of pure, bulk SiO 2 and it has been suggested that the interfacial layer is substoichiometric SiO 2 or a metal silicate [5][6][7]. Recent medium energy ion-scattering and electron energy-loss spectroscopy (EELS) studies found no evidence for silicate formation [8,9].…”
mentioning
confidence: 99%